2014
DOI: 10.1097/mot.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of transplant biopsies and immune responses following Treg cell therapy

Abstract: Purpose of review Regulatory T cells (Treg) are now well established as vital participants in maintaining self tolerance and preventing autoimmunity. Tregs have already been shown to be effective in preventing graft-versus-host disease in clinical bone marrow transplantation, and numerous animal studies have suggested a therapeutic role for Treg in solid organ transplantation. Recent advances in Treg isolation and expansion have the field poised to perform trials of therapeutic Treg infusion in solid organ tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The association between the complement pathway and Tregs has been well reported ( 59 ). Tregs play a crucial role in maintaining immune tolerance in both preclinical studies and are also associated with improved long-term transplant outcomes in clinical studies ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between the complement pathway and Tregs has been well reported ( 59 ). Tregs play a crucial role in maintaining immune tolerance in both preclinical studies and are also associated with improved long-term transplant outcomes in clinical studies ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the first studies focused on the inhibition of effector T-cell (Teff) priming by Tregs in secondary lymphoid organs, it has been reported that the Treg response adapts to the immune response (i.e., Th1, Th17, Th2, and Tfh cells), and that Tregs show further specialization in peripheral tissues via tissue repair and homeostasis [ 3 6 ]. In animal models, Tregs play a central role in promoting and maintaining allograft tolerance [ 7 9 ]. Kim and Lahl et al [ 10 , 11 ] demonstrated that Tregs participate in the maintenance of immune self-tolerance and homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Tregs represent less than 10 % of CD4 + T cells, which therefore make up about 13×10 9 cells in the whole body [56]. A ratio of Tregs to effector T cells of 1:3 showed a positive outcome in biopsies of rats [57]. Lower ratios were more connected to rejection.…”
Section: Number Of Tregs Neededmentioning
confidence: 99%
“…From studies in animal models, we know that the best effect is observed when Tregs are given in a prophylactic manner prior to or at the time of transplantation [5,7,57,63]. Here, the aim is to prevent acute rejection of allogeneic transplants and to induce tolerance very often without concomitant use of other immunomodulatory agents.…”
Section: Clinical Indications For Adoptive Treg Therapymentioning
confidence: 99%